Safety of Longer Size Stent in Treating De-Novo Long Coronary Lesion: Outcome at 1.5 Years Follow-Up, A Single Center Experience - Islam, AHM Waliul; Munwar, Shams; Bhuiyan, Azfar H; Reza, AQM; Talukder, Sahabuddin; Ahmed, Tamzeed; Islam, Nighat; Siddique, Atique Bin; Yousuf, Intekhab; Rahman, Zia Ur; Alam, MS (Bangladesh Heart Journal, 2018)
Background: Percutaneous coronary intervention (PCI) of long lesions by long single stent or overlapping multiple stent might have higher incidences of ISR due to increased metal burden as well as coronary intervention increase cost of hospital stay. Therefore, our primary aim of our study was to evaluate the longterm safety of treating long lesion by a single longer size stent and its follow-up by coronary angiogram and or clinical evaluation at our OPD. Methods: patient who had gone through PCI from the year 2014 to mid Oct 2017 at our center, had longer lesion and were treated by more than 38mmstent were selected and analyzed. Total 255(Male 213: Female 42) patients were enrolled in this study, underwent elective PCI and follow up CAG at on average 1.5 yrs. Total 267 stents were deployed in 255 patients, in some of the patient had double vessel disease to treat. Mean age for both male: female was(55 :56) yrs. Associated Coronary artery disease (CAD) risk factors were Dyslipidemia, Hypertension, Diabetes Mellitus, Positive FH for CAD and Smoking (all male), CKD, Hypothyroidism. Results: Among the study group; 192 (75.3 %) were hypertensive; 189(74.1%) were Dyslipidemic, 126(49.4%) patients were Diabetic, positive FH 74(29.4 %), CKD 8 (3.1%), Hypothyroidism 2 (0.8%) and 104(40.8%) were all male smoker. Common stented territory was, LAD 126(49.4%), RCA 115(45.1%), and LCX 24(9.4%).Among the total patient population, Single vessel stented were 236 (92.5%) and DVD 19 (7.5%). Total 267 stents were deployed, among them 48mm were in total 159 (59.6%); among 40 mm were stented in 61(22.8%) and 38 mm in 47(17.6%) vessels. At an average follow-up period of 1.5 years, all stented territory remain patent without any residual stenosis. Conclusion: We conclude that treating de-novo coronary long lesion by a single longer size stent is safe without any residual stenosis at an average followup period of 1.5 yrs. Thus, to reduce chances of recurrent ISR, hospital re-admission and reduce hospital cost as well. Bangladesh Heart Journal 2018; 33(2) : 106-111